Analysis of intake air temperature effect on performance of portable atmospheric water generation (PAWG) systems with heat sink angle orientation of 75o - Muhamad Jafri; Ben Vasco Tarigan; Hairman Sahrudin Lanae (Politeknik Negeri Lhokseumawe, 2023)
The increasing demand for clean water and the diminishing supply of clean water sources can result in a clean water crisis. Air is a ubiquitous, inexpensive, and clean water source. Using Atmospheric Water Generators (AWG), the water contained in the air can be extracted. This study's objective was to determine the effect of inlet air temperature and air heater power variations on tool performance and PAWG condensate water production at a condenser angle of 75 degrees. The procedure utilized is experimental on three PAWG boxes. Each box has a distinct temperature at its entrance. The variation of inlet air temperature is accomplished by heating the air before it enters the box with an air heater; the applied power variations are 0.484 Watt, 0.964 Watt, and 1.702 Watt. The results demonstrated that variations in air heater power and inlet air temperature affected system performance and condensate water production. Maximum water discharge and PAWG performance were achieved when the air heating power was 0.48 watts and the water discharge was 1.166 milli liters per hour. At 0.0084 ml/h/W, the PSys system performance had the highest value. The variable air heating power of 0.946 Watt represents the utmost COP value of PAWG. This power variable has a high temperature difference and influences the COP value at high levels.